Corynebacterium diphtheriae and Related Toxigenic Species Genomics, Pathogenicity and Applications - Burkovski, Andreas (Springer Netherlands : Imprint: Springer, 2014)
Corynebacterium diphtheriae is the classical etiological agent of diphtheria and the type strain of the genus Corynebacterium. While diphtheria of the respiratory tract became rare with the introduction of vaccination programs in industrialized countries, even today several thousand cases per year are reported to the World Health Organization. This shows that diphtheria is not completely eradicated and that reservoirs exist. The book summarizes the latest advances made in understanding C. diphtheriae and the closely related species Corynebacterium ulcerans and Corynebacterium pseudotuberculosis. Topics addressed are genomics of toxigenic corynebacteria, host-pathogen-interaction, detection, surveillance and treatment as well as application aspects.